Who's in favour? Same-sex union laws in parliament. Issue 3 (2nd July 2016) - Hildebrandt, Achim
ABSTRACT: The article analyses which parties support registered partnership and same-sex marriage bills in parliament in Western Europe. Existing comparative research indicates that left parties back same-sex union laws. This article shows that support is not limited to the left camp. Liberal and even Christian democratic parties have expressed above-average support as well, albeit with certain exceptions. The chief opponents of same-sex union laws are Protestant parties and the parties of the far right; in terms of numbers, however, both are largely insignificant. Far more relevant for these laws' chances of success are the positions of the large parties at the centre and at the right of the political spectrum. The analysis reveals considerable inter-country differences in these parties' attitudes, which can be explained to a large extent with the two-worlds-of-morality-politics distinction introduced by Engeli, Green-Pedersen and Larsen: countries in which centre and right parties continue to oppose same-sex union laws are part of the religious world, with the exception of France. The results for France indicate a need for further research.